2021
DOI: 10.1101/2021.04.14.439812
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the Effect of Flow Compensation and Quantitative Susceptibility Mapping Method on the Accuracy of Venous Susceptibility Measurement

Abstract: Quantitative susceptibility mapping (QSM) is a promising non-invasive method for obtaining information relating to the oxygen metabolism. However, the optimal acquisition sequence and QSM reconstruction method for reliable venous susceptibility measurements are unknown. Full flow compensation is generally recommended to correct for the influence of venous blood flow, although the effect of flow compensation on the accuracy of venous susceptibility values has not been systematically evaluated. In this study, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…On the other hand, the improved performance of the iLSQR algorithm seems to be mainly benefiting from minimizing streaking artifacts in the reconstructed susceptibility maps 46 . However, we observed that this algorithm produced lower susceptibility levels in GP (compared with other reconstruction methods), which coincides with a previous study that reported lower estimation of venous susceptibility using the iLSQR 70 . This may originate from the concept the iLSQR employs to suppress streaking artifacts that involves estimating and subtracting the artifacts from an initial susceptibility map, which may alter the contrast of strong susceptibility sources 46 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, the improved performance of the iLSQR algorithm seems to be mainly benefiting from minimizing streaking artifacts in the reconstructed susceptibility maps 46 . However, we observed that this algorithm produced lower susceptibility levels in GP (compared with other reconstruction methods), which coincides with a previous study that reported lower estimation of venous susceptibility using the iLSQR 70 . This may originate from the concept the iLSQR employs to suppress streaking artifacts that involves estimating and subtracting the artifacts from an initial susceptibility map, which may alter the contrast of strong susceptibility sources 46 .…”
Section: Discussionsupporting
confidence: 89%
“…46 However, we observed that this algorithm produced lower susceptibility levels in GP (compared with other reconstruction methods), which coincides with a previous study that reported lower estimation of venous susceptibility using the iLSQR. 70 This may originate from the concept the iLSQR employs to suppress streaking artifacts that involves estimating and subtracting the artifacts from an initial susceptibility map, which may alter the contrast of strong susceptibility sources. 46 Thus, the iLSQR might not be the best choice for applications that involve estimating strong susceptibility sources, and other methods could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Where 24 Five subjects were scanned twice within the same session without repositioning to enable image-based calculation of magnitude and phase SNRs.…”
Section: Methodsmentioning
confidence: 99%
“…All volunteers provided written informed consent, and the local research ethics committees approved the experimental sessions. Images were acquired using a transverse orientation, FOV = 240×240×144 mm 3 , voxel size = 1‐mm isotropic, flip angle = 20 0 , TR = 29 ms, 5 evenly spaced echoes (TE 1 /TE spacing = 3/5.4 ms), bandwidth = 270 Hz/pixel, SENSE 23 factors = 2/1.5, flyback gradients = on, no flow compensating gradients, total scan duration = 04:37 min:s 24 . Five subjects were scanned twice within the same session without repositioning to enable image‐based calculation of magnitude and phase SNRs.…”
Section: Methodsmentioning
confidence: 99%
“…All the volunteers provided written informed consent, and the local research ethics committees approved the experimental sessions. Images were acquired using a transverse orientation, field of view=240×240×144 mm 3 , voxel size=1-mm isotropic, flip angle=20□, repetition time=29 ms, five evenly spaced echoes (TE 1 TE spacing=3/5.4 ms), bandwidth=270 Hz/pixel, SENSE (23) factors=2/1.5, flyback gradients=on, no flow compensating gradients, total scan duration =04:37 min:s (24). Five subjects were scanned twice within the same session without repositioning to enable imagebased calculation of magnitude and phase SNRs.…”
Section: Methodsmentioning
confidence: 99%